2016
DOI: 10.3847/0004-637x/831/2/184
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Star Mass–radius Constraints of the Quiescent Low-Mass X-Ray Binaries X7 and X5 in the Globular Cluster 47 Tuc

Abstract: We present Chandra/ACIS-S subarray observations of the quiescent neutron star (NS) low-mass X-ray binaries X7 and X5 in the globular cluster 47Tuc. The large reduction in photon pile-up compared to previous deep exposures enables a substantial improvement in the spectroscopic determination of the NS radius and mass of these NSs. Modeling the thermal emission from the NS surface with a non-magnetized hydrogen atmosphere and accounting for numerous sources of uncertainties, we obtain for the NS in X7 a radius o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 90 publications
(167 reference statements)
8
142
0
Order By: Relevance
“…9. Sources with higher counts in the 2-6 keV range, notably W42 (X9), seem to show an increased luminosity in this work, whereas sources with lesser counts in this hard band, notably W46 (X7), seem to show a decreased luminosity (though spectral fitting shows that W46/X7 has demonstrated that it is not actually variable; Bogdanov et al 2016). A likely explanation is the reduced sensitivity of the ACIS-S detector in the lower energy bands, which combined with a single assumed spectral model can produce such apparent variations.…”
Section: Source Catalogmentioning
confidence: 85%
See 3 more Smart Citations
“…9. Sources with higher counts in the 2-6 keV range, notably W42 (X9), seem to show an increased luminosity in this work, whereas sources with lesser counts in this hard band, notably W46 (X7), seem to show a decreased luminosity (though spectral fitting shows that W46/X7 has demonstrated that it is not actually variable; Bogdanov et al 2016). A likely explanation is the reduced sensitivity of the ACIS-S detector in the lower energy bands, which combined with a single assumed spectral model can produce such apparent variations.…”
Section: Source Catalogmentioning
confidence: 85%
“…While the five 2000 observations (described in Grindlay et al 2001a) were carried out with the ACIS-I CCD array at telescope focus, the eight 2002 observations (described in H05) and the six 2014-15 observations (described in Bogdanov et al 2016) were acquired with the ACIS-S CCD array. All the 2014-15 observations, as well as short observations in 2000 and 2002, were taken using a subarray, which reduced the frame time, and thus reduced "pile-up"-the (incorrect) recording of two photons which landed on nearby pixels during one frame as a single event.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be achieved by comparing measured masses (Demorest et al 2010;Antoniadis et al 2013) and radii (Guillot et al 2013;Guillot & Rutledge 2014;Heinke et al 2014;Nättilä et al 2015;Bogdanov et al 2016;; see Özel & Freire 2016 for a recent review) to the predictions of particular EOS. However, this approach is limited in scope, as it serves to constrain the parameters of already formulated EOS frameworks and may not necessarily span the full range of possibilities.…”
Section: Introductionmentioning
confidence: 99%